Atypical presentation of recurrent varicella zoster virus infection: A case report and review of the literature - Sumanas Bunyaratavej (2018)
© 2015, SEAMEO TROPMED Network. All rights reserved. Recurrent varicella infection is rare but has been reported in immunocompromised patients. We present a patient with atypical recurrent varicella infection who had disseminated central crusting papular lesions without dermatomal distribution. Serology showed previous varicella zoster virus (VZV) infection and the lesions were positive for VZV DNA, consistent with recurrent VZV infection. Atypical recurrent varicella infection is probably an under-recognized condition. VZV infection should be considered in the differential diagnosis of ecthyma-like lesions in an immunocompromised host.